Learning Model on Social Science Education Assisted by YouTube Channel in Digital Era - Sudrajat, Ajat; Darojat, Ojat; Kustandi, Cecep (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to develop and test the effectiveness of the YouTube Channel application-assisted learning model in improving the understanding of Open University Elementary School Teacher Education Study Programme students of Basic Social Studies Concepts. This research uses the Borg & Gall model which involves ten stages, ranging from initial research to product dissemination. Data were collected through questionnaires and interviews with students and lecturers. The results showed that the YouTube Channel-assisted learning model significantly improved students' understanding. The experimental group that used the learning video showed a higher increase in comprehension scores than the control group. The average score increase in the experimental group reached 25 points, while the control group only experienced an increase of 11 points. This research concludes that YouTube Channel-based learning is an effective media to improve students' understanding of Basic Concepts of Social Studies material. In addition, this study also identified positive responses from students regarding the use of learning videos, which are considered more interesting and easier to understand abstract concepts. It is recommended that this learning model be implemented more widely at the Open University and developed for other courses